Learning Organization and Feedback Culture in Patient Safety Incident Reporting: The Mediating Role of Non-Punitive Response - William, Wilko; Liana, Duta; Jusat, Idrus (Yayasan Jompa Research and Development, 2025)
This study originated from initial observations at RSIA Santo Yusuf North Jakarta, which highlighted the importance of evaluating the extent to which feedback culture and learning organization influence healthcare workers’ behavior in reporting patient safety incidents. The purpose of this research is to analyze the influence of feedback culture and learning organization on patient safety incident reporting, with non-punitive response as an intervening variable. The study employed a quantitative approach using a survey method and path analysis technique. The research sample consisted of 95 nurses and midwives at RSIA Santo Yusuf North Jakarta. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. The results indicate that Feedback Culture (X1) and Learning Organization (X2) have a positive and significant effect on Non-Punitive Response (Z), with coefficients of 0.445 (p = 0.000) and 0.386 (p = 0.000), respectively. Non-Punitive Response (Z) also significantly influences Patient Safety Incident Reporting (Y) (β = 0.200; p = 0.004). In addition, Feedback Culture (X1) directly affects Incident Reporting (Y) (β = 0.218; p = 0.001), while Learning Organization (X2) shows the strongest direct effect (β = 0.387; p = 0.000). These findings emphasize the importance of strengthening feedback culture, fostering organizational learning, and ensuring non-punitive responses to improve the quality of patient safety incident reporting. Practically, this research contributes by providing hospital management with evidence-based insights to design interventions, policies, and training programs that encourage open communication and create a supportive culture for healthcare professionals in reporting incidents.